Physical activity as an alternative or adjunct to menopausal hormone therapy for symptom management in women with primary ovarian insufficiency - Lopez-Pizarro, M (ELSEVIER IRELAND LTD, 2026)
Background: Physical activity alleviates menopausal symptoms in women whose menopause occurs after the age of 45; however, its effect in primary ovarian insufficiency, which occurs before the age of 40, remains unknown. Objective: To examine the association between physical activity, menopausal symptoms, and the use of menopausal hormone therapy in women with primary ovarian insufficiency. Methods: We analysed data from 4708 participants from two studies conducted in 12 Latin American countries. After applying eligibility criteria, 564 women with primary ovarian insufficiency (351 idiopathic and 213 surgical) were included. Menopausal symptoms were assessed using a validated scale, and severe symptoms were defined according to established cut-offs. Physical activity was classified according to international recommendations for moderate-intensity activity. Logistic regression models were adjusted for sociodemographic, clinical, and lifestyle variables. Results: The prevalence of severe menopausal symptoms was 39.2%, with no significant difference between idiopathic and surgical primary ovarian insufficiency. Women with severe symptoms were less likely to meet recommended levels of physical activity or to be current users of menopausal hormone therapy. In adjusted models, regular physical activity (OR 0.65; 95% CI 0.45-0.94) and current use of menopausal hormone therapy (OR 0.27; 0.17-0.42) were associated with a lower likelihood of severe symptoms, whereas obesity and use of psychotropic medication were associated with a higher likelihood. Conclusions: Women with primary ovarian insufficiency who engage in regular physical activity or currently use menopausal hormone therapy report less severe menopausal symptoms. Regular exercise may be an important non-hormonal option for women who cannot or prefer not to use hormone therapy.